Multi-scale structural inheritance of fracture systems pattern in coal-bearing measures of the Lorraine-Saar coal Basin - В.О. Привалов; Ж. Піронон; Ф. де Донато; Р. Мішель; А. Ізар; C. Morlot; О.А. Панова (Геофизический журнал, 2022)
The Lorraine-Saar Basin (LSB) is one of the major Paleozoic coalfields of Western Europe that has been shapedover two centuries as a heartland of underground coal mining and associated industrial activities in the transborderarea of France and Germany. The Basin still has considerable coal reserves accumulated in numerous laterally continuous coal seams that were affected by processes of thermogenic production of gaseous hydrocarbons during post-Carboniferous burial and related coalification. The LSB stands out by its up to 6 km sedimentary column and its inversion resulting in Paleozoic erosion in the range of 750 m (French part of the Basin) and pre-Mesozoic (Permian) erosion between 1800 and 3000 m (German part of the Basin). Historically, coal production in the Lorraine and the Saar portions of the entire Basin was associated with numerous mining hazards because of the high methane content in coal seams. The LSB has the potential to host an enormous unconventional resource base including coalbed methane (CBM). Coal mines here are no longer operated to produce coal; however, methane generated in deep compartments is venting here via fracture swarms to the Earth’s surface. Cutting natural methane emissions throughout CBM production within coal-bearing terrains is a crucial opportunity for slowing global warming rates. Nearly all CBM plays worldwide are affected in some way by natural multiscale fracture sets ranging from large fault zones to closely spaced joints, micro-shears, or cleat sets in coal seams. The LSB is not excluded indeed from this trend because of the long-term experience of geological exploration during extensive coal mining in the past. Characterization of structural patterns of fracture networks at different scales is a pragmatic process boosting the reliable perception of the performance of coalbed methane gas reservoirs. The focus of this contribution is to get an insight into the style and kinematic description of the multi-scale fault and cleat patterns in the LSB based on results of subsurface and underground geological mapping, and X-ray computer tomography. It will benefit the right mindset to ensure proper technical decisions for efficient exploration and exploitation of CBM reservoirs in the Basin.